Innovative process combining roasting and tempering to mechanically dehull jicaro seeds (Crescentia alata K.H.B). (November 2017) - Corrales, Carla V.; Achir, Nawel; Forestier, Nelly; Lebrun, Marc; Maraval, Isabelle; Dornier, Manuel; Perez, Ana M.; Vaillant, Fabrice; Fliedel, Geneviève
Abstract: An innovative process combining roasting and tempering was proposed to promote puffing and mechanical dehulling of jicaro seeds. Roasting was performed at three temperatures (120 °C, 140 °C, and 160 °C) and for six residence times (80–180 s). A previous seed tempering was performed at 15% moisture content for 24 h, by spraying the seeds with an amount of water calculated to reach the final moisture content of 15%. The following parameters were monitored as a function of time to optimize the roasting operation: percentage of open seeds, whiteness of cotyledons, and content of two volatile compounds, 2, 5-dimethylpyrazine and ethyl-2-methylbutyrate which are considered as the key jicaro note. The optimal roasting was achieved at 160 °C for 150 s with 90% open seeds. The optimal mechanical dehulling was achieved after tempering the roasted seed at 10% moisture content with a yield of 75%. The lightness evolution followed a zero-order kinetic with an activation energy of 103 kJ mol −1 . Ethyl-2-methylbutyrate and 2, 5-dimethylpyrazine increased with the temperature and period of roasting. Graphical abstract: Highlights: Roasting was optimized and combined with tempering to mechanically dehull seeds. Dehydration followed first-order kinetics, caused puffing and enabled 90% seed open. Optimal roasting preserved key aroma and limited L-value loss to less than 10%. Ethyl-2-methylbutyrate and 2, 5-dimethylpyrazine increased with roasting temperature. Dehulling performance depended on the number of open seeds and their tempering.